Teknologi Pembuatan Lateks Dadih Melalui Proses Penggetaran - Yasinta, Yasinta; Edison, Rachmad; Maryanti, Maryanti (Politeknik Negeri Lampung, 2019)
Obstacles factor to get natural rubber raw materials is less efficient for latex processing into concentrated latex, because it need a long time that 2-3 weeks. Centrifugation method many used by concentrated latex factory because it can concentrate the latex with a short relatively time. While the weakness of the centrifugation method is more expensive if that compared with the curdling. With the weakness centrifugation method and curdling, in this research, making the concentrated latex are used vibration method, with the addition of curdle. The purpose of this research is to get the optimum vibrations speed for the concentrated latex manufactured, the speed of the vibrations are used 150 rpm, 175 rpm, 200 rpm, 225 rpm and 250 rpm. The design are used in this research is Randomized Block Design with 6 treatments was repeated 4 times, then obtained 24 units of the experiment, if there is a real difference, then used the BNT at the level of 5% and the data analysis process using Minitab version 16. the most optimum RPM are used in this research is 225 with a quality approaching the standard. Keywords: latex, concentrated latex, vibration, cmc